Small cell and large cell neuroendocrine carcinoma of the larynx: A comparative analysis. (August 2019) - Strojan, Primož; Hernandez-Prera, Juan C.; Beitler, Jonathan J.; Eisbruch, Avraham; Saba, Nabil F.; Mendenhall, William M.; Nieto, Carlos Suarez; Smee, Robert; Rinaldo, Alessandra; Ferlito, Alfio
Highlights: A systematic review of the literature for period 1972–2019. 141 articles with 273 cases were reviewed and analyzed. Differences exist between SCNEC and LCNEC in clinical characteristics and prognosis. Most effective treatment for poorly differentiated NECs is yet to be determined. The LCNECs seems to bear more favorable prognosis than SCNECs. Abstract: The poorly differentiated neuroendocrine carcinomas (NECs) of the larynx are rare tumors that comprise of a small cell-type (SCNEC) and a large cell-type (LCNEC). In order to consolidate the current knowledge about their characteristics and management a systematic review of the available literature was performed. The PubMed/Medline and Scopus databases search resulted in 141 articles published between 1972 and 2019, describing 273 patients: 230 cases were of SCNEC histology (84.2%) and 43 cases were LCNECs (15.8%). Comparing both histological entities, patients with LCNECs were older (63.2 vs. 58.7 years, p = 0.036) than SCNEC patients and had more often primary tumor in a supraglottic larynx (79.5 vs. 56.1%, p = 0.039), advanced-stage neck disease (N2-3, 56.8 vs. 40%, p = 0.061), surgery-based treatment (83.7 vs. 51.9%, p < 0.001) and had no radiotherapy (44.2 vs. 29%, p = 0.071). At presentation, systemic metastases were diagnosed in 12.1% of the patients, whereas disease relapse was experienced by two-thirds (65.3%) of those initially staged M0 ; systemic relapse, alone or in combination with local/regional recurrence, was the most frequent type of failure (in 71.9%). On multivariate analysis, more advanced disease stage and SCNEC histology adversely influenced disease-specific survival. Wide variations in the pattern of care, including radiotherapy doses and chemotherapy regimens, were found among long-term survivors without known disease at ≥ 24 months of follow-up (N = 36). We conclude that the most effective treatment for poorly differentiated NECs has yet to be determined.